2019
DOI: 10.4103/ijmr.ijmr_214_18
|View full text |Cite|
|
Sign up to set email alerts
|

Antimicrobial susceptibility profile & resistance mechanisms of Global Antimicrobial Resistance Surveillance System (GLASS) priority pathogens from India

Abstract: Antimicrobial resistance is a major concern globally. Infections due to drug-resistant pathogens are becoming difficult and a challenge to treat. As treatment choices are limited due to the high-drug resistance rates, there is an increase in the health care cost, duration of hospital stay, morbidity and mortality rates. Understanding the true burden of antimicrobial resistance for a geographical location is important to guide effective empirical therapy. To have a national data, it is imperative to have a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 93 publications
4
36
1
2
Order By: Relevance
“…Of the primary alignments to OXA genes on plasmids in the Vellore hospital effluent (OXA-1, OXA-164, OXA-181, OXA-392, OXA-58), one (OXA-181) was an OXA48-like allele. E. coli isolates in hospitals in India also contained resistance genes to other classes of antibiotics that we identified using metagenomic sequencing on plasmids in the Vellore hospital effluent, including tetA and tetB, dfrA17, sul1, and catB3 61 .…”
Section: Occurrence Of Pathogens and Antibiotic Resistance In Boston And Vellorementioning
confidence: 96%
“…Of the primary alignments to OXA genes on plasmids in the Vellore hospital effluent (OXA-1, OXA-164, OXA-181, OXA-392, OXA-58), one (OXA-181) was an OXA48-like allele. E. coli isolates in hospitals in India also contained resistance genes to other classes of antibiotics that we identified using metagenomic sequencing on plasmids in the Vellore hospital effluent, including tetA and tetB, dfrA17, sul1, and catB3 61 .…”
Section: Occurrence Of Pathogens and Antibiotic Resistance In Boston And Vellorementioning
confidence: 96%
“…In the Asia-paci c region, ve distinct sequence types (STs); ST59, ST30, ST72, ST8, and ST772 are the predominant and often spread to hospitals [5]. In India, MRSA accounts for 37% of S. aureus infections [6,7]. However, very few studies have reported the molecular epidemiology of S. aureus.…”
Section: Introductionmentioning
confidence: 99%
“…Bizim çalışmamızdaki MRSA oranının (%38,3) Türkiye geneli ve Avrupa ülkeleri ortalamasından yüksek olduğu görülmektedir. Buna karşılık, Uzakdoğu ülkelerinden Hindistan' da yapılan direnç sürveyans çalışmasında MRSA izolatlarının oranı ülkemizden ve Avrupa ülkelerinden daha yüksek (% 40) olarak bulunmuş, ayrıca S. aureus izolatları arasında %5,8 VISA ve %6,9 hVISA izolatı olduğu bildirilmiştir(13).Enterococcus spp:…”
unclassified